Examination of Electromagnetic Radiation Intensity of 5G Mobile Transceivers Based on Its Operational Techniques - ADEOGO, Johnson O. (FUDMA Journal of Engineering and Technology, 2026)
Electromagnetic Radiation (EMR) absorption is a major worrisome for both network users and providers. Due to the technological progression that produced 5G networks, the proliferation of antennas and the multiplication of mobile transceivers of different brands around us every day give portable/mobile network operators multiple access to EMR. Mobile transceivers’ operational techniques in energy radiation reduction are one of the key features to be examined in Fifth Generation (5G) systems to decrease the levels of Electromagnetic Radiation (EMR) around the users. In measuring electromagnetic radiation in terms of Power Density (PD) from mobile transmitters used, a Radio Frequency (RF) meter was employed, and the distance of 5 cm to 30 cm between the measuring equipment and the transmitters used with the help of a meter rule. During routing for connection, Itel gave the lowest radiation level of 0.3255mW/cm2 and the highest radiation level is from Apple iPhone 12, which is 0.4400mW/cm2. The results obtained were validated using the Excel package, and none of the transmitters used radiated above the international standard of non-ionising radiation level of 0.45 mW/cm2. This is important for the reduction of EMR levels to avoid excessive absorption of electromagnetic radiation.
Keywords: Electromagnetic Radiation, Intensity, Distance and Operational Techniques.